Dark curse - Feehan, Christine (Feehan, Christine. Carpathian novel., 2008)
Now the world's leading expert in the field of ice-cave study, Lara is on a search for healing microorganisms, but also for the source of her nightmares - the cold, dark corners of her childhood. Only one man has the will and the power to help her: Nicolas De La Cruz. Dangerous and arrogant, centuries of hunting and killing have taken their toll on him but he still longs to feel sensual love without the hunger for blood. A tenuous trust emerges between Lara and Nicholas, and a passion neither of them has ever experienced but, as much as they long for a future as lifemates, they are also haunted by the unknown dangers of the dark curse.